2013
DOI: 10.2174/1874620901306010068
|View full text |Cite
|
Sign up to set email alerts
|

Infant Sleep Development: Location, Feeding and Expectations in the Postnatal Period

Abstract: Abstract:Coping with sleep disruption is a common difficulty faced by new parents. Here we take a critical, contextual and evolutionary perspective on recent evidence surrounding the development of normal infant sleep in the postnatal period, its relationship with feeding method and the relevance of sleep location. Firstly, we explore the question of defining 'normal' infant sleep, considering the timing of sleep consolidation, cross-cultural and historical perspectives, and the impact of feeding method on inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 121 publications
(136 reference statements)
1
5
0
1
Order By: Relevance
“…Nurses' support of breastfeeding also involved talking with parents whose expectations about newborn sleeping and breastfeeding patterns were not congruent with actual behavior. Parents were unprepared for their newborns' nocturnal schedule, a finding supported in other research (Russell et al, 2013;Weddig et al, 2011). Consistent with recommendations from other researchers, these night nurses suggested teaching parents during the day about expected newborn behaviors such as infant feeding cues and sleep patterns (DaMota et al, 2012;Heinig, 2010;Russell et al, 2013;Schmied et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nurses' support of breastfeeding also involved talking with parents whose expectations about newborn sleeping and breastfeeding patterns were not congruent with actual behavior. Parents were unprepared for their newborns' nocturnal schedule, a finding supported in other research (Russell et al, 2013;Weddig et al, 2011). Consistent with recommendations from other researchers, these night nurses suggested teaching parents during the day about expected newborn behaviors such as infant feeding cues and sleep patterns (DaMota et al, 2012;Heinig, 2010;Russell et al, 2013;Schmied et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Although 24hour rooming in is considered best practice, newborns in the United States continue to be placed in hospital nurseries during the night to allow their mothers to rest, particularly in hospitals without a BFHI designation (Nickel et al, 2013;Schmied et al, 2011;Weddig et al, 2011). However, researchers found that removing newborns from their mothers' rooms during the night did not result in an increase in quality or duration of mothers' sleep but did result in decreased infant sleep, more crying, less frequent breastfeeding, and decreased breastfeeding initiation and breastfeeding rates (Keefe, 1987(Keefe, , 1988Russell, Robinson, & Ball, 2013;Svensson, Matthiesen, & Widström, 2005;Waldenström & Swenson, 1991;Weddig et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Infant feeding method affects infant sleep (Russell et al., 2013), but research findings are inconclusive because studies use very different ages with different results. Some studies find that formula-fed infants sleep more than breastfed infants (Huang et al., 2015), while others show infants who breastfeed do not necessarily get less sleep than formula-fed infants (Doan et al., 2007; Engler et al., 2012; Pennestri et al., 2018; Ramamurthy et al., 2012), even if they wake more (DeLeon & Karraker, 2007; Galbally et al., 2013; Mindell et al., 2012; Weinraub et al., 2012).…”
Section: The Medical View Of Infant Sleepmentioning
confidence: 99%
“…In a sample of 6,410 mothers, Kendall‐Tackett et al () found that mothers who mixed‐fed breast milk and formula, or only formula‐fed their babies, reported fewer hours of sleep, as well as lower physical energy and higher rates of depression. Explaining that it's normal for babies to have fragmented sleep, to need to be fed often at night and to want to be close to a caregiver can be extremely helpful to parents trying to cope with sleep issues postpartum (Russell, Robinson, & Ball, ).…”
Section: The Evidencementioning
confidence: 99%